Experimental treatments to attenuate blood spinal cord barrier rupture in rats with traumatic spinal cord injury: A meta-analysis and systematic review - Deng, Li; Lv, Jun Qiao; Sun, Lin (Frontiers in Pharmacology, 2022)
Background: Traumatic spinal cord injury (t-SCI) is a severe injury that has a devastating impact on neurological function. Blood spinal cord barrier (BSCB) destruction following SCI aggravates the primary injury, resulting in a secondary injury. A series of experimental treatments have been proven to alleviate BSCB destruction after t-SCI. Methods: From a screen of 1189 papers, which were retrieved from Pubmed, Embase, and Web of science, we identified 28 papers which adhered to strict inclusion and exclusion criteria. Evans blue (EB) leakage on the first day post-SCI was selected as the primary result. Secondary outcomes included the expression of tight junction (TJ) proteins and adhesion junction (AJ) proteins in protein immunoblotting. In addition, we measured functional recovery using the Basso, Beattie, Besnahan (BBB) score and we analyzed the relevant mechanisms to explore the similarities between different studies. Result：The forest plot of Evans blue leakage (EB leakage) reduction rate: the pooled effect size of the 28 studies was 0.54, 95% CI: 0.47–0.61, p<0.01. This indicates that measures to mitigate BSCB damage significantly improved in reducing overall EB leakage. In addition TJ proteins (Occludin, Claudin-5, and ZO-1), AJ proteins (p120 and β-catenin) were significantly upregulated after treatment in all publications. Moreover, BBB scores were significantly improved. Comprehensive studies have shown that in t-SCI, inhibition of matrix metalloproteinases (MMPs) is the most commonly used mechanism to mitigate BSCB damage, followed by endoplasmic reticulum (ER) stress and the Akt pathway. In addition, we found that bone marrow mesenchymal stem cell-derived exosomes (BMSC-Exos), which inhibit the TIMP2/MMP signaling pathway, may be the most effective way to alleviate BSCB injury. Conclusion：This study systematically analyzes the experimental treatments and their mechanisms for reducing BSCB injury in the early stage of t-SCI. BMSC-Exos, which inhibit MMP expression, are currently the most effective therapeutic modality for alleviating BSCB damage. In addition, the regulation of MMPs in particular as well as the Akt pathway and the ER stress pathway play important roles in alleviating BSCB injury.